Reevaluation of Self-Expanding Metal Stents as a Bridge to Surgery for Acute Left-Sided Malignant Colonic Obstruction: Six Years Experience - Ribeiro,Iolanda (2016)
Introduction: Self-expanding metal stents (SEMS) as a bridge to surgery have been used as an alternative for acute malignant left-sided colonic obstruction. However, the benefits are uncertain. The European Society of Gastrointestinal Endoscopy no longer recommends their use in patients with low surgical risk because of the risk of tumor recurrence. Methods: Patients admitted for acute malignant left-sided colonic obstruction who underwent SEMS as a bridge to elective surgery or urgent surgery were retrospectively evaluated. Postoperative morbidity/mortality, stent complications and survival were recorded. Our aim was to compare the outcome between preoperative SEMS and direct emergent surgery in acute left-sided malignant colonic obstruction. Results: 42 patients were included (SEMS group: 27 and surgery group: 15). There were no differences between groups in relation to age, ASA classification and tumor stage. The technical success of SEMS was 88.9% and the clinical success was 85.2%. There were three SEMS related perforations. In the surgery group, the stoma rate was higher (86.7% vs 25.9%, p < 0.001) and there was a trend for a lower length of hospital stay (18.9 days vs 26.3 days, p = 0.051). SEMS verses surgery group: There were no differences in the rate of temporary stoma (57.1% vs 61.5%, p = 0.84), definitive stoma (42.8% vs 38.5%, p = 0.84), success of primary anastomosis (86.7% vs 66.7%, p = 0.22) and Clavien-Dindo classification (≥III: 36% vs 58.2% p = 0.24). Overall survival at 1/5 years was identical in the two groups 100%/56% in the SEMS group vs 93%/43% in the surgery group, p = 0.14), as well as tumor recurrence at 3/5 years (24%/50% vs 20%/36% respectively, p = 0.68). Conclusions: SEMS are associated with a lower overall stoma rate and a higher primary anastomosis rate. However, there are no differences in complications, overall survival and recurrence between the groups.